Regulated Spatial Distribution of Cyclooxygenases and Lipoxygenases in Crohn's Ulcer - Yao Mao; Jian'an Ren; Jieshou Li (Mediators of Inflammation)
Background and Aims. Arachidonic acid metabolism actively participates in the initiation, climaxing, and resolution phases of inflammation, and its close connection with inflammatory bowel diseases has been only recently discovered. We aimed to clarify the role of different arachidonic pathways and the interrelationships between them in Crohn's disease. Methods. Seventeen specimens of Crohn's disease dated between 2003/1/1 and 2005/1/1 were collected and underwent immunohistochemical analyses with cylcooxygenase 1, cyclooxygenase 2, 5-lipoxygenase, and 15-lipoxygenase-1 antibodies. Results. (1) The spatial distribution of the three leading enzymes in arachidonic acid pathway—cyclooxygenase 2, 5-lipoxygenase, and 15-lipoxygenase-1—followed sequential arrangement in Crohn's ulcer: neutrophils highly expressing 5-lipoxygenase were in the utmost surface which bordered the band of cyclooxygenase-2 expression that is located just beneath it, and in the lower layers and below the granulation region were eosinophils carrying 15-lipoxygeanse-1. (2) Cyclooxygenase-2 and 15-Lipoxygenase-1-positive cells formed two barrier-like structures that possibly inhibited neutrophil infiltration. Conclusion. The regulated distribution indicated coordinated interplay between inflammatory cells and parenchymal cells, between arachidonic acid pathways, and between innate and adaptive immunity; and the barrier-like structures indicated protective roles for cyclooxygenase 2 and 15-Lipoxygenase-1 in Crohn's disease.